Gap‐coupled designs of star shape microstrip antennas for dual band and wide band circular polarized response. Issue 5 (22nd January 2019) - Deshmukh, Amit A.; Doshi, Akshay; Odhekar, Anuja A.
Abstract: Gap‐coupled designs of star‐shape microstrip antennas for dual band and wide band circular polarized response are proposed. An angular displacement between fed and parasitic patches yields the optimum separation between patch orthogonal resonant modes to yield circular polarized response. In dual band design, axial ratio bandwidth of 8% is obtained whereas wideband design gives axial ratio bandwidth of nearly 29%. Proposed configurations exhibit broadside pattern with peak gain of more than 7 dBi. Resonant length formulations for star shape patch and for their dual and wide band designs are presented. They provide guidelines for redesigning similar antenna at different frequency.